BERPIKIR POSITIF DAN DUKUNGAN KELUARGA TERHADAP PENYESUAIN DIRI MAHASISWA PERTUKARAN PELAJAR KAMPUS MERDEKA - Siti Nuzulul Rochmah; Eko Hardi Ansyah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This research was conducted with the aim of observing the influence of positive thinking and family support on the adjustment of overseas students participating in the batch 2 student exchange program. This study used a quantitative method with 140 students from all cities in Indonesia as subjects who were recorded in the Independent Campus Student Exchange Batch program. 2 which is determined by random sampling technique. Data was collected by giving three scales to the subject, namely the positive thinking scale, family support scale, and self-adjustment scale which are reliable and valid. The results of data analysis in this study used multiple regression which showed that there was a positive influence between positive thinking and family support together on self-adjustment in batch 2 exchange students.